IMF conditionality and structural reforms: Evidence from developing countries - Ablam Estel Apeti; Kwamivi Gomado (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2023)
The global economy, dominated by the consequences of a disastrous health crisis and international tensions, needs policy support to regain its growth dynamic. To regain an inclusive and sustainable growth dynamic, structural policies of governments are needed to allow a reallocation of resources and to stimulate productivity. International cooperation seems to be necessary, and the International Monetary Fund's (IMF) contribution could play an important role in promoting reforms. Indeed, in IMF-supported programmes, the conditions for developing countries' transition to liberalization and open markets are often common. In this paper, we address the question of whether periods of IMF conditionality contribute to the promotion of structural reforms in developing countries. We combine a rich dataset on IMF conditionality and structural reforms covering 64 developing countries over the period 1980-2014. Through the entropy balancing method and alternative identification strategies, we show that IMF conditionality programmes promote structural reforms in developing countries. We show that the effect of IMF conditionality can vary depending on the type of conditionality, the type of reform, the time frame, the initial level of structural reforms, and can depend on some structural factors including the business cycle, the quality of fiscal and monetary policy, the level of development, and the quality of institutions. Furthermore, we show that IMF conditionality can have spillover effects on trading partners and that IMF conditionality programmes that are met tend to have a greater impact on structural reforms.
Keywords: F33; F34; O24; O43; 330; IMF conditionality; structural reforms; developing countries; initial conditions; entropy balancing